Early gut colonisation by Bifidobacterium breve and B. catenulatum differentially modulates eczema risk in children at high-risk of developing allergic disease - Ismail, Intan Hakimah; Boyle, Robert J.; Licciardi, Paul V.; Oppedisano, Frances; Lahtinen, Sampo; Roy M., Robins Browne; Tang, Mimi L. K. (Wiley, 2016)
BACKGROUND: An altered compositional signature and reduced diversity of early gut microbiota are linked to development of allergic disease. We investigated the relationship between dominant Bifidobacterium species during early postnatal period and subsequent development of allergic disease in the first year of life.